Fatigue study of partially overlapped circular hollow section K-joints. Part 2 : experimental study and validation of numerical models - Chiew, Sing Ping (2014)
In the second part of this study, the reliability of the geometrical models and the mesh generation procedure developed in Part 1 are validated by comparing the modelling results with full scale tests results. Static tests were applied to study the stress concentration factors while fatigue tests were applied to study the stress intensity factor and the fatigue life of the joints. The results obtained indicated that the uncracked joint model could lead to reliable stress concentration factor estimations while the cracked joint models could lead to conservative stress intensity factor and residual fatigue life predictions close to experimental results.